Models for the Spatial Development of Medium-Sized Cities in Poland in the Era of Transformation as Exemplified by Puławy, Płock and Siedlce - Czerny, Mirosława; Czerny, Andrzej (Olsztyn Economic Journal, 2019)
Post-1990, urbanisation in Poland took on new forms and features not very clearly on display in urban space before that time. Alongside a dynamic process of suburbanization encompassing ever-greater areas around large cities, there has also been a phenomenon attesting to the occurrence of similar trends of the expansion of built-up areas with urban functions into areas around small and medium-sized urban centres. Taking shape are new wedges of urban construction pushing their way into suburban and rural areas. These are arising along access roads leading between the smaller cities and the large regional centres. It is not only services and industry that are located along these (as was shown in the classical model after Hoyt), since there are also estates of single-family or multi-family housing. The aim of the work described here has thus been to analyse the processes referred to as they are exemplified by the Polish towns or cities of Płock, Siedlce and Puławy. The comparative method deployed in this work is to lead to a proposal for a model of the development of Poland’s urban centres of medium size.